AAV-mediated YAP expression in cardiac fibroblasts promotes inflammation and increases fibrosis - Jamie Francisco (Nature Portfolio, 2021)
Abstract Fibrosis is a hallmark of heart disease independent of etiology and is thought to contribute to impaired cardiac dysfunction and development of heart failure. However, the underlying mechanisms that regulate the differentiation of fibroblasts to myofibroblasts and fibrotic responses remain incompletely defined. As a result, effective treatments to mitigate excessive fibrosis are lacking. We recently demonstrated that the Hippo pathway effector Yes-associated protein (YAP) is an important mediator of myofibroblast differentiation and fibrosis in the infarcted heart. Yet, whether YAP activation in cardiac fibroblasts is sufficient to drive fibrosis, and how fibroblast YAP affects myocardial inflammation, a significant component of adverse cardiac remodeling, are largely unknown. In this study, we leveraged adeno-associated virus (AAV) to target cardiac fibroblasts and demonstrate that chronic YAP expression upregulated indices of fibrosis and inflammation in the absence of additional stress. YAP occupied the Ccl2 gene and promoted Ccl2 expression, which was associated with increased macrophage infiltration, pro-inflammatory cytokine expression, collagen deposition, and cardiac dysfunction in mice with cardiac fibroblast-targeted YAP overexpression. These results are consistent with other recent reports and extend our understanding of YAP function in modulating fibrotic and inflammatory responses in the heart.